Chronic hypoxia in pregnant mice impairs the placental and fetal vascular response to acute hypercapnia in BOLD-MRI hemodynamic response imaging. (July 2021) - Ginosar, Yehuda; Bromberg, Zohar; Nachmanson, Nathalie; Ariel, Ilana; Skarzinski, Galina; Hagai, Lital; Elchalal, Uriel; Shapiro, Joel; Abramovitch, Rinat
Abstract: Introduction: Brief hypercapnic challenge causes acute placental hypoperfusion with fetal brain sparing on BOLD-MRI. We hypothesize that this non-invasive imaging strategy can distinguish between normal pregnancy and chronic placental hypoperfusion (using the maternal hypoxia model). Methods: Eighteen pregnant female ICR mice were randomized to three groups: normoxia, late-onset hypoxia (12%O2 ;E13.5–17.5) and early-onset hypoxia (12%O2 ;E10.5–17.5). On E17.5, animals were imaged in a 4.7-T Bruker-Biospec MRI scanner. Fast coronal True-FISP was performed to identify organs of interest (placenta and fetal heart, liver and brain). BOLD-MRI was performed at baseline and during a 4-min hypercapnic challenge (5%CO2 ). %-change in placental and fetal signal was analyzed from T2*-weighted gradient echo MR images. Following MRI, fetuses and placentas were harvested, weighed and immuno-stained. Results: In normoxic mice, hypercapnia caused reduction in BOLD-MRI signal in placenta (−44% ± 7%; p < 0.0001), fetal liver (−32% ± 7%; p < 0.0001) and fetal heart (−54% ± 12%; p < 0.002), with relative fetal brain sparing (−12% ± 5%; p < 0.0001). These changes were markedly attenuated in both hypoxia groups. Baseline fetal brain/placenta SI ratio was highest in normoxic mice (1.14 ± 0.017) and reduced with increasing duration of hypoxia (late-onset hypoxia: 1.00 ± 0.026; early-onset hypoxia: 0.91 ± 0.016; p = 0.02). Both hypoxic groups exhibited fetal growth restriction with prominent placental glycogen-containing cells, particularly in early-onset hypoxia. There was increased fetal neuro- and intestinal-apoptosis in early-onset hypoxia only. Conclusions: BOLD-MRI with brief hypercapnic challenge distinguished between normoxia and both hypoxia groups, while fetal neuroapoptosis was only observed after early-onset hypoxia. This suggests that BOLD-MRI with hypercapnic challenge can identify chronic fetal asphyxia before the onset of irreversible brain injury. Highlights: Chronic maternal hypoxia caused placental injury with fetal growth restriction in mice. In normoxia, hypercapnic challenge elicited placental and fetal organ hypoperfusion in BOLD-MRI. Hypercapnia-induced changes in BOLD-MRI were markedly reduced in both chronic hypoxia groups. By contrast, fetal brain apoptosis was elevated only in early-onset chronic maternal hypoxia. BOLD-MRI hypercapnic challenge identifies fetal hypoperfusion before onset of neuroapoptosis.